Consensus Recommendations on GLP-1 RA Use in the Management of Type 2 Diabetes Mellitus: South Asian Task Force - Kalra, Sanjay (Diabetes Ther, 2019)
The advent of incretin mimetics such as glucagon-like peptide-1 receptor agonists (GLP-1 RAs) has enriched the armamentarium for diabetes management owing to their glycaemic as well as extra-glycaemic benefits. The approval status and availability of this class of drugs vary widely across the globe. Being a relatively newer class of drug with numerous benefits, several national and international guidelines are working towards addressing clinical questions pertaining to the optimal use of GLP-1 RAs for the management of diabetes. Although the newer class of drugs are associated with significant benefits such as patient-centric approach, these drugs demand the providers to be vigilant and knowledgeable about the medication. The South Asian population is at higher risk of type 2 diabetes mellitus (T2DM) because of their genetic predisposition and lifestyle changes. Hence, prevention and management of T2DM and its associated complications in this population are of paramount importance. The current report aims to present an overview of current knowledge on GLP-1 RAs based on pragmatic review of the available clinical evidence. In addition, this report is a consensus of expert endocrinologists representing South Asian countries including India, Pakistan, Bangladesh, Nepal, Sri Lanka, Afghanistan and the Maldives on essential recommendations related to the use of GLP-1 RAs in a real-world scenario. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13300-019-0669-4) contains supplementary material, which is available to authorized users.